First person - Karishma Chhabria (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Karishma Chhabria is first author on 'Sodium nitroprusside prevents the detrimental effects of glucose on the neurovascular unit and behaviour in zebrafish', published in DMM. Karishma conducted the research described in this article while a PhD student in Tim Chico and Clare Howarth's lab at University of Sheffield, UK. She is now a postdoc in the lab of David Kleinfeld at UCSD, USA, investigating how the brain achieves precise spatio-temporal blood-flow regulation.